Design and Implementation of the External Quality Assurance System Application Case Study of the National University Quality Assurance Agency: Design and Implementation of the External Quality Assurance System Application Case Study of the National University Quality Assurance Agency - Ahmad Deni Maulana; Mohammad Iwan Wahyuddin; Sari Ningsih (Jurnal Mantik, 2020)
This study aims to describe the implementation of the application of the External Quality Assurance System (SPME) case study of the National University Quality Assurance Agency. In this case the SPME application is managing website-based document management so that it can support SPME performance. Data collection is done by qualitative methods, namely through observation, interview, and documentation. The results of the study are as follows (1) Campus can implement an external quality assurance application system, (2) In implementing the system, the data and information used are correct and accurate so that it can support SPME activities in the campus environment, (3) All activities implementing the external quality assurance system can be documented.